Engineering Chemisorption of Fe4 Single‐Molecule Magnets on Gold. Issue 24 (12th November 2021) - Poggini, Lorenzo; Tancini, Erik; Danieli, Chiara; Sorrentino, Andrea Luigi; Serrano, Giulia; Lunghi, Alessandro; Malavolti, Luigi; Cucinotta, Giuseppe; Barra, Anne‐Laure; Juhin, Amélie; Arrio, Marie‐Anne; Li, Weibin; et al.
Abstract: Gaining control over the grafting geometry is critically important for any application of surface‐supported single‐molecule magnets (SMMs) in data storage, spintronics, and quantum information science. Here, tetrairon(III) SMMs with a propeller‐like structure are functionalized with thioacetyl‐terminated alkyl chains to promote chemisorption on gold surfaces from solution and to evaluate differences in adsorption geometry and magnetic properties as a function of chain length. The prepared monolayers are investigated using X‐ray absorption techniques with linearly and circularly polarized light to extract geometrical and magnetic information, respectively. All derivatives remain intact and form partially oriented monolayers on the gold surface. A ligand‐field analysis of the observed X‐ray natural linear dichroism shows that the threefold molecular axis is invariably biased toward the surface normal, in agreement with ab initio calculations. This preferential orientation is most pronounced in monolayers of the shortest‐chain derivative, which are further studied with an ultralow temperature X‐ray magnetic circular dichroism setup operating down to 350 mK. The isothermal field sweeps with the magnetic field at normal incidence show an open hysteresis loop below 1 K, while measurements at different incidence angles prove the magnetic anisotropy of the monolayers. Abstract : Thioacetyl‐terminated alkyl chains of different length are introduced in tetrairon(III) single‐molecule magnets in order to promote a controlled chemisorption on gold surfaces. Synchrotron‐based experiments and theoretical tools are used to probe differences in molecular orientation and magnetic properties on the surface as a function of tether's length.